Blackening Canada : diaspora, race, multiculturalism - Barrett, Paul, 1979- (University of Toronto Press, 2015)
Focusing on the work of black, diasporic writers in Canada, Blackening Canada investigates the manner in which literature can transform conceptions of nation and diaspora.